The state of research and publication at a Philippine University baseline date for enhanced research and development initiatives - Fontejon-Bonior, Gina A. (Silliman Journal, 2009)
This paper reviews the literature on whether productivity in research and publication should be considered a standard in higher education institutions. Moreover, it discusses the national, institutional, and personal barriers to faculty engagement in research and publication and strategies that facilitate such productivity. Finally, findings on an investigation on the state of research and publication at a Philippine University are presented. The study aims to determine [1] the percentage of college teachers who are productive in research and publication; [2] the factors that facilitate and constrain research and publication productivity; and [3] mechanisms and infrastructure that are already in place in the University and how these may be enhanced to further stimulate a culture or research and publication. Results show that from 1997-2007, only 47% of the faculty engaged in research, of which only 29% have published their output in scholarly publications. Among the commonly identified reasons for the lack of productivity are [1] teaching tasks; [2] lack of necessary writing skill needed to produce a published report; [3] housework and family responsibility; [4] lack of knowledge on how to repackage their theses/dissertation to meet the technical and requirements of of particular journals; and, [5] absence of information on the procedures and dynamics of getting a work published. Those who are productive cited the following as the factors that stimulate in research and publication: [1] the belief that research is integral to their professional growth as a teacher; [2] accreditation; [3] incentives for research; and [4] promotion in rank. The following strategies were suggested by the respondents to strengthen the culture of research and publication in the University: [1] establishing a mentoring system where faculty members who have already conducted research and published their research findings closely supervise and coach those who have not yet engaged in research and publication; [2] crediting at least six units to faculty who engage in research, the credit awarded only once the output has been published in scholarly journals; [3] conducting workshops on how to get a work published in appropriate journals; [4] facilitating a system of wider and more frequent dissemination of research and development opportunities from concerned offices; and, [5] identifying more funding agencies to support research and development activities of the faculty.